Habituasi Literasi Baca Tulis Siswa di Sekolah Dasar (Literational Habituation of Students to Read Write in Elementary School) - Umi Atun Sholikhah; Markhamah Markhamah; Laili Etika Rahmawati; Endang Fauziati (Jurusan Tadris Bahasa Indonesia, 2023)
This study aims to describe literacy habituation in elementary schools which includes implementation, obstacles, and solutions. This qualitative research uses data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use interactive analysis. The results of the study show that the implementation of literacy in Indonesian language learning in elementary schools complies with the provisions of the Ministry of Education, Culture, Research, and Technology. The obstacles encountered were the low literacy culture of students, the lack of utilization of facilities and infrastructure by students, and the teacher did not provide examples of literacy habituation. The solution is in the form of providing a library, using teaching aids, using information technology media, fun literacy programs and activities, providing reading corners, teachers choosing appropriate books for students, and forming reading clubs.Penelitian ini bertujuan untuk mendeskripsikan habituasi literasi baca tulis di Sekolah Dasar yang meliputi pelaksanaan, hambatan, dan solusi. Penelitian kualitatif ini menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi Teknik analisis data menggunakan analisis interaktif. Hasil penelitian menunjukkan bahwa pelaksanaan literasi baca tulis pada pembelajaran bahasa Indonesia di Sekolah Dasar sudah sesuai dengan ketentuan dari Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi. Hambatan yang dihadapi berupa rendahnya budaya baca tulis pada siswa, kurangnya pemanfaatan sarana dan prasarana oleh siswa, guru tidak memberikan contoh habituasi literasi baca tulis. Solusinya berupa penyediaan perpustakaan, penggunaan alat peraga, pemanfaatan media teknologi informasi, program dan aktivitas literasi yang menyenangkan, penyediaan sudut baca, guru memilihkan buku yang layak untuk peserta didik, serta pembentukan klub membaca.